Intralymphatic Histiocytosis: An Unusual Presentation - Timothy J. Blackwell; Zachary Ingersoll; Martin Blackwell (Karger Publishers, 2021)
Intralymphatic histiocytosis (ILH) is a rare cutaneous condition initially described in 1994 by O'Grady et al. It often appears as a red to violaceous, livedoid patch or plaque usually on the extremities. We present a 71-year-old female with a history of psoriasis, 50 pack years smoking and recent Legionnaires disease who came to us complaining of a red to violaceous, blanching, edematous, mildly tender lesion covering the left lower lip and extending to the chin and anterior neck. After multiple biopsies, ILH was confirmed and the patient was initially started on tacrolimus 0.1% ointment b.i.d., but there was no response. Then, she was started on oral pentoxifylline and intermittent topical steroids, as well as continuing the topical tacrolimus. There was again no response, so now she is taking a TNF-ɑ inhibitor as it appears to be a granulomatous process. These ILH cases are very rare and there is limited literature that describes one treatment as a cure. Treatment of ILH is very difficult, but several different therapies have been reported with varying success. If the disease is secondary to an underlying inflammatory disease or malignancy, then treatment of the primary disorder can lead to resolution of the ILH.